Government Actions And The Mineral Industry (The National Institute for Occupational Safety and Health (NIOSH), 1980)
Law of the Sea. - The Ninth Session of the Law of the Sea Conference resumed July 28 at Geneva and will run for 5 weeks. The 160-nation Conference began in 1973. Two of the major factors to be discussed are the transfer of technology to the UN-controlled Enterprise or mining authority, and how the 36-member Council will make decisions. As the session completed its third week, delegates expressed little hope of completing a treaty text this year. There was a feeling, though, that substantive issues might be settled so that a treaty text can be completed next year. The Deep Seabed Hard Mineral Resources Act signed by the President on June 28, provides an interim regulatory procedure for ocean mining activities conducted by U.S. nationals that may be superseded by a law of the sea treaty.